Diastereoselective One-Pot Tandem Synthesis of Chromenopyridodiazepinones through 1,4- and 1,6-Aza-Conjugate Additions/Heterocyclizations - Bouchama, Abdelghani; Hassaine, Ridha; Talhi, Oualid; Taibi, Nadia; Mendes, Ricardo F.; Almeida Paz, Fillipe A.; Bachari, Khaldoun; Silva, Artur M. S. (Synlett, 2018)
We report an efficient one-pot synthesis of a novel series of chromenopyridodiazepinone polyheterocycles by a catalyst-free nucleophilic addition of ethane-1,2-diamine to (E,E)-3-[3-(2-hydroxyphenyl)-3-oxoprop-1-en-1-yl]-2-styrylchromones at room temperature under mild conditions. The reaction proceeds by a tandem process involving 1,4- and 1,6-aza-conjugate additions of one amino group of ethane-1,2-diamine to the α,β-unsaturated (3-oxoprop-1-en-1-yl) and the α,β,γ,δ-diunsaturated (2-styrylchromone) carbonyl system of the precursor, followed by imine condensation of the remaining amino group to generate the chromenopyridodiazepinone polyheterocycle. All compounds were characterized by means of one- and two-dimensional NMR spectroscopy and single-crystal X-ray crystallography.
Keywords: styrylchromones; ethanediamine; chromenopyridodiazepinones; one-pot synthesis; tandem reaction; aza-conjugated addition